GROWTH AND SURVIVAL OF SEEDLINGS AND SAPLINGS IN THE LOGGED - OVER FOREST, KINTAP, SOUTH KALIMANTAN - Yusuf S. Jafarsidik (Indonesian Journal of Forestry Research, 2004)
A study on demography,  growth  and survival of  seedlings and saplings was conducted  in the Hutan Kintap  concenssion,   South Kalimantan,   Indonesia. The aim of  the study  was to monitor  pattern  of growth of seedlings and saplings among different types of logged -  over forest, including the newly  logged  -  forest, older  logged  -  over forests   (treated and untreated),   and un-logged-forest    patches.   The  study began in 1991, and nineteen  of  0.25  ha plots   were set up in a total  of  six blocks  designated   as consecutively  A, B, C, D, E and F.  Block A was a newly logged   forest and had five plots,  and Block  B -  D were in forest which  had been logged  in 1979.  Block B (five plots) had received no silvicultural   treatment,  while Block  C (five plots) and  D (one plot)   had  been  lightly   thinned  after  felling and  further  Block C received  a further  thinning treatment   Block  E (one plot)  had been  heavily   thinned,  and Block F (2 plots)   was an un-logged   control. The  density  of  seedling  varied within  the study sites, and averaged  from  47,000 ha"  to 121,000   ha·1•   The mean height increment  of  seedlings varied among block ranging from 2.9  cm year'  to 10.5  cm year".  Block A had the highest general  mean  increment  of  10.5  cm year",   followed  in decreasing  order  by Block C of 5.4 and Block F, 4.5  cm year".  Growth  of  seedling in Block  B was low, even lower  than  the growth  in the un-logged   Block F. The  difference  of the increment among Block A, B, C and F however was not significant. The liberation treatment  in Block C significantly   resulted in a higher (p<0.01)  increment  (5.4 cm year") than that in  the untreated  Block  B (2.9 cm year").  Seedling  mortality ranged from 16 to 37 % year", and declined with  height   class. The  mortality  of  seedlings  might  be related  among  other  factors  to the  humidity  and density  of  seedlings per-unit  area. The  density  of  sapling ranged  from 6,800 ha" to 7,700  ha" and they had diameter  growth  of  0.8 mm  year" to  2.2  mm year",  and height   growth  of  12.6  cm year" to 21.8  cm year"1. The  difference  in the  diameter  increment   among  block  r\, B,  C and  F was  not  significant.    The  average sapling height increment  varied (but not significantly so) among Block,  ranging from 12.6  cm year" in Block A to 21.8  cm year" in Block C. Mortality  of  sapling was relatively   low  in all block.  Higher  mortality  in the un-logged   forest  Block  I' and  in the untreated  Block B might  due to  the low  degree  of  canopy   opening.